Determinants of Student Achievement in Economic Learning - Mokhammad Wahyudin; Lindawati Lindawati; Mohammad Hisyam Yahya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Student academic achievement is influenced by various internal and external learning factors that shape students’ readiness, behavior, and support systems. This study aims to examine the effects of learning interest, learning discipline, learning style, learning facilities, and parental attention on the academic achievement of Class X E students in Economics at SMAN 1 Sumber Cirebon. This study used a quantitative survey design. The population consisted of all 96 students in Class X E, and total sampling was applied so that all students became respondents. Data were collected through questionnaires and documentation, then analyzed using multiple linear regression with SPSS version 15. The findings show that learning discipline and parental attention have positive and significant effects on students’ academic achievement. Learning interest shows a positive direction but does not have a statistically significant partial effect. Learning style and learning facilities also do not show significant partial effects. These results indicate that students’ achievement in Economics is more closely related to disciplined learning behavior and family support than to learning preferences or facilities alone. The study concludes that schools need to strengthen learning discipline, build students’ learning interest, and encourage parental involvement to support better academic achievement.